ANALISIS VIABILITAS LACTOBACILLUS LACTIS PADA INOVASI MEDIA DASAR PERTUMBUHAN ALTERNATIF DAN MEDIA DASAR PENEPUNGAN BAKTERI ASAM LAKTAT - Sulastri, Ani; Manguntungi, Baso (Jurnal TAMBORA, 2020)
The limited shelf life in a food requires a natural preservative so that the food used is not easily damaged and has a longer shelf life, namely by using lactic acid bacteria (BAL) using alternative media. By using lactic acid bacteria, the time in the storage period food products can be extended. The purpose of this study was to determine the viability of the Lactobacillus lactis bacteria on an alternative growth base media and a media on the media of bacteria. Lactic acid bacteria were rejuvenated and culture propagation of 5 ?l was inoculated into 5 mL of MRSB media. Formulation media used for bacterial growth such as whey tofu + 5% sucrose + 1% urea. The alternative media was incubated for 24 hours. Bacterial growth was observed at 0, 4, 8 and 16 hours using the TPC (Total Plate count) method. Various media Lactobacillus lactis bacterial deposition was grown on MRSB media and dried with freeze dry for 48 hours and the viability of Lactobacillus lactis was tested. The basic growth media that can be used are Lactobacillus lactis bacteria, namely whey tofu + sucrose 5% + urea 1% as well as Lactobacillus lactis viability results in various media which are grown on MRS media and various alternative media shows that the media has a 100% carrageenan composition able to maintain the viability of Lactobacillus lactis cells.